Od edukowania do rodzicielskiego działania. O dostrzeganiu problemów, gotowości poszukiwania rozwiązań i podejmowaniu ryzyka w edukacji szkolnej dziecka - Lulek, Barbara (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Current social and cultural changes make it harder for individuals to act on their own. Moreover, parents’ separation from teachers affects adversely executing of young generation’s educational and upbringing processes. Conjoint decision making – the actual decision making in major educational matters, as well as educational partnership are increasingly emphasized. This article is a compilation of theoretical and empirical study. The author presents results of research carried out in primary schools in Podkarpacie province from 2013 to 2015. The author categorises parental activity and places it on the scale of educational participation. By isolating areas of parental engagement, the author indicates that referring to parents’ knowledge about cooperation, partnership or dialogue is insufficient, since the knowledge is often incomplete or conventional, at the same time trying to point out practical solutions which would enable coexistence of parents, teachers and parental community. It is a sort of parental path between praxis and techne.
Keywords: child; education; family; school